Evaluation and Strategy to Strengthen the Implementation of Early Detection of Cervical Cancer Using the IVA Test Method - Fitriani, Sulastri; Ramadhani, Nur Rizky; Susanti, Eva; Guspianto, Guspianto (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: The cervical cancer poses a significant global health threat with a noteworthy prevalence rate. Early detection through Acetic Acid Visual Inspection (IVA) has proven effective in reducing mortality rates and improving patient prognosis. However, the implementation of this early detection method stil faces challenges. Objective: This study aims to evaluate the implementation of VIA in the province of Jambi and devise improvement strategies. Method: A mixed-method approach was carried out, combining quantitative analysis through the assessment of Primary Health Centers (Puskesmas) and qualitative analysis through interviews with stakeholders. Results: The evaluation of IVA implementation reveals positive assessments in input (54.8% excellent, 37% good) and process (72.6% excellent, 27.4% good). There was variations in output were observed with 58.9% excellent, 21.9% good, 13.7% fair, and 5.5% unsatisfactory. However, improvements were still needed in input quality and program implementation to enhance overall output results. Conclusion: It is recommended to increase regional monitoring efforts, cooperation and partnerships, participation of community leaders, mass outreach and campaigns, increased budget allocation and supervision Keywords: Cervical Cancer; Early Detection; Evaluation Strategy